(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Moral Integrity as a Foundation of Contemporary Public Discourse Moral integrity is a necessity for anyone engaged in public service, because it gives credibility to public discourse and creates a special bond of trust with those who have placed their hope in those who have a vocation to lead. Moral integrity is the factual expression of a moral axiology that has its foundation only in faith. Ethical systems cannot offer this, because they are the creation of man, are therefore autonomous, and represent the temporal interests of some ideologies or philosophies. While moral systems are of theonomes, and their principles spring from Revelation. We need moral integrity, honest leaders who can take on the challenges of contemporaneity and overcome them!